TAFSIR SAYYID QUṬB DALAM PERSPEKTIF KONTEKSTUAL: REKONSTRUKSI MAKNA DAN IMPLIKASI SOSIALNYA - Siti Nurlaila; Yeni Andriyani; Ridho Rahmatullah; Muhammad Nikola Shidqi; Andi Rosa (STKIP Subang, 2025)
This study examines the construction of the meaning of justice in Sayyid Quṭb's interpretation through his monumental work, Fī Ẓilāl al-Qur'ān, and its implications for contemporary socio-political dynamics. Departing from Quṭb's unique interpretation, which combines literary, spiritual, and movement-oriented (ḥarakī) dimensions, this study analyzes how the concept of justice is reconstructed as a fundamental principle in building a society based on divine ḥākimiyyah. Using qualitative methods based on literature and a hermeneutic approach, this study examines Quṭb's interpretation of several key verses on justice, such as QS. an-Nisā’ [4]: 58, 135; QS. al-Mā’idah [5]: 8; and QS. al-Ḥujurāt [49]: 9, to see how the concept of justice is formulated as a demand of faith and an instrument of social change. The results of this study indicate that Quṭb read verses on justice thematically and critically, linking them to a critique of modern socio-political structures, which he considered a new form of ignorance (jahiliyyah). His interpretation has broad implications for shaping modern Islamic political discourse, particularly regarding moral awareness, the concept of the ideal state, and demands for transformative justice. Thus, Sayyid Quṭb's interpretation not only offers a textual reading of the Qur'an but also presents a socio-political paradigm that continues to influence contemporary Islamic movements.